Optimization of electrospinning parameters for producing carrageenan-PVA based nanofibers film - Noor Fitrah, Abu Bakar; Mohd Aizuddin, Salihfudin; Nur Hidayati, Hidayati Othman; Fatmawati, Adam; M. Nazli Nazli, Naim; Nur Hashimah, Alias; Norazah Abd A., Abd Rahman (Society of Fiber Science and Technology, 2023)
Formulation of K-Carrageenan/polyvinyl alcohol (PVA) based and optimization of electrospinning parameters for producing electrospun nanofibre were investigated. Two types of PVA polymers; fully hydrolyzed (FH) and partially hydrolyzed (PH), were used as crosslink agents or co-polymer with the ratio of K-Carrageenan to PVA was 70 : 30. Nanofibers with K-Carrageenan/PVA FH blend produced a uniform and smooth nanofiber at 12 w/v % of PVA FH concentration. Both types of PVA promoted the hydrophilicity of the nanofiber with a slight absorption rate for K-Carrageenan/PVA PH nanofiber. The formulation of 1 w/v % K-Carrageenan and 12 w/v % PVA FH was used to optimize the electrospinning parameters by varying voltage, distance and flowrate using response surface methodology (RSM). The optimum electrospinning parameters for voltage, distance and flowrate for the respective formulation were 15.07 kV, 12.40 cm, and 0.435 ml/h, respectively.